Capitania de Itamaracá, poder local e conflito: Goiana e Nossa Senhora da Conceição (1685-1742) - Barbalho, Luciana de Carvalho (2009)
After the village of Goiana became a villa and head of the Itamaracá s captaincy, in 1685, it started a conflict with the old headquarters, Nossa Senhora da Conceição Island, where the both villas elites had a conflict because of this title. Wherever, it happened, in Goiana, another confront between the land s nobles and the port s mascates, by the occupation of the officers of councilors; confront that stayed more violent with the explosion of the Mascates War in Pernambuco. The interest s play between the two social strata of Goiana and the Crown s agents of the neighboring captaincy, it solidified a way to achieve favors of the Crown s agents in Pernambuco, to strengthen the nobles in Goiana, in the sense politics, reaching, in 1742, its emancipation like a head of the captaincy . Observing the political conflicts in the Itamaracá s captaincy and this one between the Pernambuco s political elites, we can realize practices that belong to a culture of the Old Regime, like the formation of the customer networks.